La investigación universitaria: propuesta de una revista radial académica. - Torres Acaro, Evelyn Alexandra (My University, 2021)
This proposal arises from the search for an answer to a problem encountered regarding the need for dissemination of research activities carried out in higher education institutions. The design of a radio magazine is proposed based on the diagnosis of a reality, the needs of students and the recommendations of experts, with the aim of strengthening university research activity. A qualitative-quantitative research was carried out: documentary and bibliographical review, observation, surveys and interviews, with an adequate analysis and synthesis to carry out the approach of a communicational product that allows the visibility of research actions carried out by students and teachers, as part of their teaching-learning process: a radio magazine of educational-scientific nature, aimed at young people , university students and citizenship in general, with a dynamic structure that contains: information, debate, interviews and advice on topics of university and citizen interest. The research shows that improvisation has no place in a university educommunicative product, since planning is required: in the short and medium term, execution strategies and permanent evaluation, among other aspects, as a basis to attract the attention of students and above all to make visible in the community, university research inside and outside the classrooms.
La presente propuesta surge de la búsqueda de respuesta a un problema encontrado respecto a la necesidad de difusión de las actividades investigativas que se realizan en las instituciones de educación superior. Se plantea el diseño de una revista radial a partir del diagnóstico de una realidad, las necesidades de estudiantes y las recomendaciones de expertos, con el objetivo de fortalecer la actividad investigativa universitaria. Se hizo una investigación cuali-cuantitativa: revisión documental y bibliográfica, observación, encuestas y entrevistas, con un análisis y síntesis adecuado para realizar el planteamiento de un producto comunicacional que permita la visibilización de acciones de investigación que realizan estudiantes y profesores, como parte de su proceso de enseñanza aprendizaje: una radio revista de corte educativo-científico, dirigido a público juvenil, estudiantes universitarios y ciudadanía en general, con una estructura dinámica que contenga: información, debate, entrevistas y consejos sobre temas de interés universitario y ciudadano. La investigación muestra que la improvisación no tiene cabida en un producto educomunicativo universitario, pues se requiere planificación: a corto y mediano plazo, estrategias de ejecución y evaluación permanente, entre otros aspectos, como base para atraer la atención de estudiantes y sobre todo visibilizar en la comunidad, la investigación universitaria dentro y fuera de las aulas de clases.
Keywords: RADIO REVISTA; EDUCACION SUPERIOR; INVESTIGACION UNIVERSITARIA